PERANCANGAN KARIKATUR DALAM HARIAN RAKYAT SUL SEL - Saputra Suaib, Rahmat (Journal of Innovation Research and Knowledge, 2025)
This study examines the design process behind Harian Rakyat SulSel's unique use of caricature as its primary visual headline. Using a qualitative descriptive method with an interpretive paradigm, this research focuses on the creative collaboration between cartoonists and editors, analyzing the complete workflow from idea development and sketching to digital execution and final approval. Data were collected through observation, in depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings show that the caricature design process is carried out through close collaboration between cartoonists and editors, utilizing digital tools such as Paint Tool SAI to ensure efficiency and visual consistency. Each caricature not only presents humor and social criticism but also conveys messages that align with the news context.. Based on Dieter Rams’ Good Design theory, the caricatures in Rakyat SulSel Daily reflect design principles focused on functionality, aesthetics, innovation, and continuous improvement. Thus, caricature design becomes an integral part of the newspaper’s visual strategy, strengthening its editorial identity and enhancing reader engagement.